Kinetic study of nordihydroguaiaretic acid recovery from Larrea tridentata by microwave-assisted extraction - Martins, S. (2010)
BACKGROUND:Nordihydroguaiaretic acid (NDGA) is a powerful antioxidantwith biological activities of great interest in several health areas, including antiviral, cancer chemopreventive, and antitumorgenic. Little information is available on extraction methods of NDGA from Larrea tridentata. Hence, the aim of this study was to develop a rapid and effective microwave-assisted extraction (MAE) method for NDGA recovery from Larrea tridentata leaves, and to compare the results obtained with those found using conventional heat-reflux extraction (HRE). RESULTS: Extraction time for similar NDGA yields was significantly reduced from 18 to 1 min when MAE was used instead of HRE. Optimum conditions for NDGA extraction (3.79 ± 0.65%) consisted in using 50% methanol as extraction solvent in a solid/liquid ratio of 1/10 gmL1. Micrographs demonstrated that the improvement in NDGA extraction by MAE might be related to a greater extent of cell rupture of the plant material. Extracts obtained by MAE exhibited antiradical activity only slightly lower than those obtained by HRE. CONCLUSIONS: MAE proved to be a faster and more efficient method for NDGA extraction from Larrea tridentata leaves than HRE. The better results for NDGA extraction by MAE might be explained by the greater extent of cell rupture of plant material during the extraction process.